Expression of aldo-keto reductase family 1 member C1 (AKR1C1) gene in porcine ovary and uterine endometrium during the estrous cycle and pregnancy - Hwang Sue-Yun; Kim Nam-Hyung; Ka Hakhyun; Seo Heewon; Kang Myung-Hwa; Nanjidsuren Tseeleema; Park Cha-Won; Sim Bo-Woong; Park Jong-Ju; Yun Seong-Jo; Kim Sang-Hwan; Naidansuren Purevjargal; et al. (BMC, 2011)
Abstract Background The aldo-keto reductase family 1 member C1 (AKR1C1) belongs to a superfamily of NADPH-dependent reductases that convert a wide range of substrates, including carbohydrates, steroid hormones, and endogenous prostaglandins. The 20alpha-hydroxysteroid dehydrogenase (20alpha-HSD) is a member of AKR family. The aims of this study were to determine its expression in the ovary and uterus endometrium during the estrous cycle and pregnancy. Methods Rapid amplification of cDNA ends (RACE) experiments were performed to obtain the 5' and 3' ends of the porcine 20alpha-HSD cDNA. Reverse-transcriptase-PCR (RT-PCR), real-time PCR, northern blot analysis, and western blot analysis were performed to examine the expression of porcine 20alpha-HSD. Immunohistochemical analysis was also performed to determine the localization in the ovary. Results The porcine 20alpha-HSD cDNA is 957 bp in length and encodes a protein of 319 amino acids. The cloned cDNA was virtually the same as the porcine AKR1C1 gene (337 amino acids) reported recently, and only differed in the C-terminal region (the AKR1C1 gene has a longer C-terminal region than our sequence). The 20alpha-HSD gene (from now on referred to as AKR1C1) cloned in this paper encodes a deletion of 4 amino acids, compared with the C-terminal region of AKR1C1 genes from other animals. Porcine AKR1C1 mRNA was expressed on day 5, 10, 12, 15 of the cycle and 0-60 of pregnancy in the ovary. The mRNA was also specifically detected in the uterine endometrium on day 30 of pregnancy. Western blot analysis indicated that the pattern of AKR1C1 protein in the ovary during the estrous cycle and uterus during early pregnancy was similar to that of AKR1C1 mRNA expression. The recombinant protein produced in CHO cells was detected at approximately 37 kDa. Immunohistochemical analysis also revealed that pig AKR1C1 protein was localized in the large luteal cells in the early stages of the estrous cycle and before parturition. Conclusions Our study demonstrated that AKR1C1 mRNA and protein are coordinately expressed in the luteal cell of ovary throughout the estrous cycle and in the uterus on day 30 of pregnancy. Thus, the porcine AKR1C1 gene might control important mechanisms during the estrous cycle.